2004
DOI: 10.1111/j.1467-9930.2004.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

At the Crossroads of Policymaking: Executive Politics, Administrative Action, and Judicial Deference by the DC Circuit Court of Appeals (1985–1996)*

Abstract: This study seeks to expand our understanding of judicial deference to administrative agencies within the context of one particularly important legal forumthe U.S. Court of Appeals for the District of Columbia. The DC circuit functions as a key venue for administrative law cases and the opinions of the court constitute a growing body of common law in the field of administrative law. We investigate the importance of several agency-centered and judge-centered variables in explaining judicial deference to administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…Kritzer et al (2002) discovered significant differences in Supreme Court behavior before and after Chevron, but also found that these differences did not always operate in the ways expected. Caruson and Bitzer (2004) found that the DC Circuit Court of Appeals was not more likely to defer to agencies when a Chevron standard of review was applied, and Smith (2005) reported no differences in Supreme Court behavior pre-and post-Chevron. Miles and Sunstein (2006: 825-6), in their analysis of both appellate and Supreme Court decisions, concluded that application of Chevron is greatly affected by judges' policy convictions, and that Chevron 'has not had the disciplining effect that it was supposed to have'.…”
Section: Ambiguity Delegation and Judicial Deferencementioning
confidence: 98%
“…Kritzer et al (2002) discovered significant differences in Supreme Court behavior before and after Chevron, but also found that these differences did not always operate in the ways expected. Caruson and Bitzer (2004) found that the DC Circuit Court of Appeals was not more likely to defer to agencies when a Chevron standard of review was applied, and Smith (2005) reported no differences in Supreme Court behavior pre-and post-Chevron. Miles and Sunstein (2006: 825-6), in their analysis of both appellate and Supreme Court decisions, concluded that application of Chevron is greatly affected by judges' policy convictions, and that Chevron 'has not had the disciplining effect that it was supposed to have'.…”
Section: Ambiguity Delegation and Judicial Deferencementioning
confidence: 98%
“…In other words, courts are more likely to defer to the agency when the perceived expertise of the agency is greater than that of the court. As Caruson and Bitzer (, 350) state, “In cases involving highly technical matters, a court is likely to defer to what has been recognized as the agency's superior subject‐matter expertise.”…”
Section: A Theory Of Appellate Court Decision Making In Unfair Labor mentioning
confidence: 99%
“…While there is a substantial body of research examining judicial review of administrative actions (Carruba and Zorn ; Caruson and Bitzer ; Cohen and Spitzer ; Cross and Tiller ; Crowley ; Humphries and Songer ; Johnson ; ; Miles and Sunstein ; Revesz ; ; Sheehan ; ; Smith ; Willison ; Wright ; Yates ), Solicitor General influence (Black and Owens ; ; ), and executive branch enforcement of court rulings (Hume ; Spriggs ; ; Wagner ), there are only a handful of empirical and qualitative studies that examine how the threat of judicial review can influence administrative behavior (Canes‐Wrone ; Howard and Nixon ; Melnick ; Seidenfeld ; Wood and Waterman ). However, none has offered a systematic study of the courts' influence on rulemaking.…”
Section: Introductionmentioning
confidence: 99%